NUMERICAL SIMULATION OF METHANE-AIR MIXTURE EXPLOSION IN 20-LITRE SPHERICAL EXPLOSION CHAMBER - Agustinus, Kevin
One of the most prominent threats in terms of occupational and operational safety in underground mining is the potential occurrence of explosions. Explosions may occur when fuel and oxygen are dispersed in a confined room accompanied by a spark of heat energy. For methane gas, the concentration range in which methane gas explosion occurs is when the concentration of methane mixed in the air is within the range of 5 to 15 percent. This way, explosions due to methane gas may occur in underground mines. The danger of methane gas explosions in underground coal mines may get even deadlier if there are other fuels that are more energy dense such as dispersed coal dust. In order to design reliable underground mine explosion prevention systems, research on the characteristics of explosions is necessary, which include methane gas. This research studies the methane gas explosion conducted using computational fluid dynamics k-epsilon model using ANSYS Fluent. This study aims to determine the maximum explosive pressure Pex, the maximum rate of increase in pressure (dP/dt)ex, and indices of explosion KG at varying concentrations of methane and oxygen in 20-litre spherical explosion chamber; to determine the effect of varying methane and oxygen gas concentrations on explosive pressures; and determine the deadliest combination of methane and oxygen gas concentrations in air under condition of complete combustion. The selection of a 20-litre ball-shaped geometry is to mimic the physical explosion chamber Siwek 20-L Chamber. Based on the research conducted, the Pex value of the study obtained varied between 4.00 bar to 6.73 bar, (dP/dt)ex varying between 26.60 bar/s to 69.43 bar/s, and indices of explosion KG varying between 16 to 39. Research shows that the concentration of methane gas, in the presence of sufficient oxygen for complete combustion, is positively correlated with explosive pressure and maximum increase in explosive pressure with time which signifies stronger explosions. The research also provides results are consistent with previous studies by stating that the deadliest concentration of methane mixture under condition of complete combustion is when the methane gas concentration at around 9.5% by volume.